Rainwater use for wash agricultural machinery and vehicles: case study of the Polytechnic School of Federal University of Santa Maria - Nogueira, Cicero Urbanetto; Nogueira, Helena Maria Camilo de Moraes; Fantinel, Antonio Luiz; Jahn, Sérgio Luiz; Padrón, Richard Alberto Rodríguez (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The studies on management and use of water resources has been one focus of several research, they are looking for alternatives to the use of natural resources and sustainability. The study aimed to planning, execution and estimate the economic return of the use of rainwater for washing vehicles, agricultural machinery and implements. The study was conducted for the sector of mechanization of the Polytechnic School of the Federal University of Santa Maria, from March 2011 to February 2013. The roof of agricultural mechanization sector has a catchment area of 215.45 m2 . Five tanks of 7000 liters each were installed. The underground water consumption was reduced by 100%. It was used 458,120.25 liters of water from rainy and intended for the proposed activities. The reservoirs were the largest investment, accounting for 63%, followed by washing 27% and 10% of total costs. A total savings of R 2009.66 was obtained and monthly R 83.74 depending on the costs of water. The system of rainwater harvesting is an alternative to reduce the consumption of water from other sources.